Effects of viscoelasticity on shear-thickening in dilute suspensions in a viscoelastic fluid. Issue 3 (11th December 2019) - Matsuoka, Yuki; Nakayama, Yasuya; Kajiwara, Toshihisa
Abstract : We investigate previously unclarified effects of fluid elasticity on shear-thickening in dilute suspensions in an Oldroyd-B viscoelastic fluid using a novel direct numerical simulation based on the smoothed profile method. Abstract : We investigate previously unclarified effects of fluid elasticity on shear-thickening in dilute suspensions in an Oldroyd-B viscoelastic fluid using a novel direct numerical simulation based on the smoothed profile method. Fluid elasticity is determined by the Weissenberg number Wi and by viscosity ratio 1 − β = η p /( η s + η p ) which measures the coupling between the polymer stress and flow: η p and η s are the polymer and solvent viscosity, respectively. As 1 − β increases, while the stresslet does not change significantly compared to that in the β → 1 limit, the growth rate of the normalized polymer stress with Wi was suppressed. Analysis of flow and conformation dynamics around a particle for different β reveals that at large 1 − β, polymer stress modulates flow, leading to suppression of polymer stretch. This effect of β on polymer stress development indicates complex coupling between fluid elasticity and flow, and is essential to understand the rheology and hydrodynamic interactions in suspensions in viscoelastic media.